2017
DOI: 10.1186/s12052-017-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

A multifactorial analysis of acceptance of evolution

Abstract: Background: Despite decades of education reform efforts, the percent of the general US population accepting biological evolution as the explanation for the diversity of life has remained relatively unchanged over the past 35 years. Previous work has shown the importance of both educational and non-educational (sociodemographic and psychological) factors on acceptance of evolution, but has often looked at such factors in isolation. Our study is among the first attempts to model quantitatively how the unique inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 34 publications
9
78
1
2
Order By: Relevance
“…Women are in the majority. This representation is a common feature of studies that utilize a 394 college undergraduate population, and is very similar to our previous study conducted at a 395 different university (Dunk et al, 2017). Students in this study tended to have a high level of 396 acceptance of evolution at the start of the fall semester, which is also similar to other studies of 397 ours, both at this university (Carter & Wiles, 2014) and elsewhere (Dunk et al, 2017).…”
Section: Number Of Respondentssupporting
confidence: 81%
See 2 more Smart Citations
“…Women are in the majority. This representation is a common feature of studies that utilize a 394 college undergraduate population, and is very similar to our previous study conducted at a 395 different university (Dunk et al, 2017). Students in this study tended to have a high level of 396 acceptance of evolution at the start of the fall semester, which is also similar to other studies of 397 ours, both at this university (Carter & Wiles, 2014) and elsewhere (Dunk et al, 2017).…”
Section: Number Of Respondentssupporting
confidence: 81%
“…Though previous research has tended to find no significant relationship between race or ethnicity 127 and evolution acceptance (Dorner, 2016;Nadelson & Hardy, 2015;Woods & Scharmann, 2001), 128 we feel it is important to include and continue to study, especially in light of Walls' (2016, p.1) 129 challenge for racially inclusive science education: "science education research aimed at 130 improving an individual's science learning and understanding necessarily must take into account 131 the background and experiences that could impact the success of such an undertaking." 132 Our prior work was among the first studies to combine most of these factors into a single 133 working model (Dunk, Petto, Wiles, & Campbell, 2017). In a midwestern public university 134 setting, we found student understanding of the nature of science to be the most significant factor 135 in our model, explaining over 13% of the unique variation in acceptance of evolution.…”
Section: Introduction 26mentioning
confidence: 86%
See 1 more Smart Citation
“…Once students pass over it, the doorway opens up a new way of thinking and processing, making the study and conduct of science easier and enabling a deeper level of understanding and making connections. Dunk et al (21) found that, of education-related factors, instruction and understanding of NOS have the greatest impact on students’ acceptance of evolution. It was the understanding of scientific thinking that seemed to change students’ minds.…”
Section: Resultsmentioning
confidence: 99%
“…As Shtulman (2006) notes, this may not be a deeplyconsidered response, because "those who do not endorse the claim that Darwin's theory of evolution has been well supported by evidence tend to endorse the alternative claim (i.e., that Darwin's theory of evolution has not been well supported by evidence) rather than plead ignorance". Furthermore, lack of knowledge of the evidence for evolution is clearly not necessarily the only, or even the most important, reason for lack of acceptance of evolution (Allmon 2011;Shtulman 2011;Nadelson 2012, 2013;Rosengren et al 2012;Dunk et al 2017). …”
Section: Introductionmentioning
confidence: 99%